EFFECT OF HEAD MANAGEMENT COMPETENCE ON TEACHER PERFORMANCE IN SMA NUSANTARA PLUS - Elysa Aryani; Alifianti Uswatun Hasanah; Hardian Dwi Putra; Zahruddin Zahruddin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to determine the effect of principal managerial competence on teacher performance at senior high school Nusantara Plus. The method used in this study is quantitative. The samples in this study were all senior high school Nusantara Plus, totaling 35 people/respondents. The data collection instrument used was a questionnaire. Based on the research results on the determination test, the coefficient of determination (R square) was 0.172. The R square value of 0.172 comes from the square of the correlation coefficient or